A Structural Model of Nitro‐Porphyrin Dyes Based on Spectroscopy and Density Functional Theory1. Issue 18 (27th July 2017) - Farley, Christopher; Aggarwal, Amit; Singh, Sunaina; Dolor, Aaron; To, Philip; Falber, Alexander; Crossley, Maxwell; Drain, Charles Michael
Abstract : Nitro‐porphyrins are an important class of commercial dyes with a range of potential applications. The nitro group is known to dramatically affect the photophysics of the porphyrin, but there are few systematic investigations of the contributing factors. To address this deficiency, we present spectroscopic studies of a series of nitro‐porphyrins, accompanied by density functional theory calculations to elucidate their structures. In particular, we explore how the positions of the substituents affect the energy levels and nuclear geometry. As expected, nitro groups on the meso‐phenyl rings cause small changes to the orbital energies by induction, while those at the β‐pyrrole positions more strongly conjugate into the aromatic system. In addition, however, we find evidence that β‐pyrrole nitro groups distort the porphyrin, creating two non‐planar conformations with distinct properties. This unexpected result helps explain the anomalous photophysics of nitro‐porphyrins reported throughout the literature, including inhomogeneous line broadening and biexponential fluorescence decay. © 2017 Wiley Periodicals, Inc. Abstract : The substitution of a nitro group onto a porphyrin compound has a large effect on the photophysical properties and potential applications of the dye. These changes are usually attributed to electronic induction and resonance, but other possible factors have not been investigated as thoroughly. In this work, the authors show that steric hindrance between the nitro group and the nearby phenyl ring causes out‐of‐plane distortions of the macrocycle which are important in understanding the electronic transitions.